Stakeholder Forum of the Sub-sector Working Group on Irrigation (SSWG-IR): the opportunities and potential of harnessing geographic information systems for irrigation management and development in Lao PDR - Inphonephong, Souphalack; Vongxay, V.; Bounnavong, K.; Phiengvilayvanh, T. (International Water Management Institute, 2025)
The first semi-annual Stakeholder Forum of 2025 of the Sub-sector Working Group on Irrigation (SSWGIR) was held in Vientiane Capital, Lao People’s Democratic Republic (Lao PDR). It was organized by the Department of Irrigation (DOI) under the Ministry of Agriculture and Environment and supported by the Asian Development Bank (ADB) together with the International Water Management Institute (IWMI). The event was attended by 80 participants from government, academia, development organizations, farmer groups, and enterprises from the banking, insurance, hydropower, and mining sectors.